What is the y-intercept of y=-4/3x+4?
1 answer:
Answer:
A. (0,4)
Step-by-step explanation:
You can calculate the y intercept when x = 0.
Substitute 0 for x:
y = (-4/3)(0) + 4
= 0 + 4
= 4
You might be interested in
Answer:
C. x = 6
Step-by-step explanation:
6 + 4 = 10
Answer:
x=16
Step-by-step explanation:
....,...................
You have a higher chance of getting a red or blue marble
Answer:
![\boxed{\sf (a + 3)(a + 1)}](https://tex.z-dn.net/?f=%20%5Cboxed%7B%5Csf%20%28a%20%2B%203%29%28a%20%2B%201%29%7D%20)
Step-by-step explanation:
![\sf Factor \: the \: following: \\ \sf \implies {a}^{2} + 4a + 3 \\ \\ \sf The \: factors \: of \: 3 \: that \: sum \: to \: 4 \\ \sf are \: 3 \: and \: 1. \\ \\ \sf So, \\ \sf \implies {a}^{2} + (3 + 1)a + 3 \\ \\ \sf \implies {a}^{2} + 3a + a + 3 \\ \\ \sf \implies a(a + 3) + 1(a + 3) \\ \\ \sf \implies (a + 3)(a + 1)](https://tex.z-dn.net/?f=%20%5Csf%20Factor%20%20%5C%3A%20the%20%20%5C%3A%20following%3A%20%20%5C%5C%20%20%5Csf%20%5Cimplies%20%20%7Ba%7D%5E%7B2%7D%20%20%2B%204a%20%2B%203%20%5C%5C%20%20%5C%5C%20%20%5Csf%20The%20%5C%3A%20%20factors%20%20%5C%3A%20of%20%5C%3A%20%203%20%5C%3A%20%20that%20%5C%3A%20%20sum%20%5C%3A%20%20to%20%5C%3A%20%204%20%20%5C%5C%20%5Csf%20are%20%5C%3A%20%203%20%20%5C%3A%20and%20%20%5C%3A%20%201.%20%5C%5C%20%5C%5C%20%20%5Csf%20So%2C%20%20%5C%5C%20%20%20%5Csf%20%5Cimplies%20%7Ba%7D%5E%7B2%7D%20%20%2B%20%283%20%2B%201%29a%20%2B%203%20%5C%5C%20%20%5C%5C%20%20%5Csf%20%5Cimplies%20%20%20%7Ba%7D%5E%7B2%7D%20%20%2B%203a%20%2B%20a%20%2B%203%20%5C%5C%20%20%5C%5C%20%20%5Csf%20%5Cimplies%20a%28a%20%2B%203%29%20%2B%201%28a%20%2B%203%29%20%20%5C%5C%20%20%5C%5C%20%5Csf%20%5Cimplies%20%28a%20%2B%203%29%28a%20%2B%201%29%20)
It would be equal to 1624